Protein-rich crackers from defatted soya flour and defatted coconut meal - Cristi, Amelia Angeles (1967)
The acceptability of sweetened and salted crackers made from a protein-rich compound of 70% defatted soya flour, 20% defatted coconut meal, 5% brewer's yeast and 5% nonfat dry milk was studied. The protein content of both the crackers and the protein-rich compound was determined by the Micro-Kjeldhal method. The compound was substituted for 70% and 95% of the all purpose flour in the original recipe for sweetened and salted crackers. Results of the subjective test showed that the crackers, both sweetened and salted, were acceptable. The sweetened crackers were more preferred than the salted ones. Results of protein analysis showed that the crackers had an exceptionally high protein content, the sweetened crackers with 70% and 95% of the protein-rich compound contained 19% and 25% protein respectively while the salted crackers contained 23% and 35% protein respectively. These values are for the crackers with nonfat dry milk. Samples without nonfat dry milk and 95% of the protein-rich compound have a theoretical value of 25% protein for the sweetened crackers and 30% for the salted crackers.